Research on Model Development for Freeway Safety Facilities. (15th March 2015) - Xie, Junping; Ma, Yongfeng; Yuan, Li
Abstract : To make freeway safety facilities function well, field survey is carried out to evaluate the maintenance quality of freeway safety facilities. In traditional models, the same weight values are assigned to the safety facilities while evaluating without considering the functional differences of different facilities. The paper develops the maintenance quality evaluation procedure and the model considering the functional differences of freeway safety facilities. In the evaluation procedure, the safety facility damage in function is the main index to get the evaluation scores for each kind of facility. The purpose of the model is to convert the evaluation scores of different safety facilities to an overall maintenance quality measure, and this result can reveal the overall facility maintenance quality of the freeway segment. In order to build the model and confirm the calculated weight of each kind of facility, Multivariable Regression and Optimized Analytic Hierarchy Process were used separately. The model was validated by comparing the proposed model evaluation results and the reorganized survey evaluation results. The coefficient of correlation ( R 2 value) is 0.9048, which shows strong correlation between the subjective evaluation and objective evaluation.